Personality traits and business environment for entrepreneurial motivation - Giorgi Zarnadze; Ines Dika; Gentjan Çera; Humberto Nuno Rito Ribeiro (Administrative Sciences, 2022)
The influences of personality traits and business barriers on entrepreneurial behaviour have been studied by numerous researchers. However, the mechanisms by which changes in institutional contexts and personality traits affect individuals' entrepreneurial motivation have not received enough attention from researchers. This paper aims to fill this gap in the literature by examining the joint effects of personality traits and business barriers on one's motivation to engage in entrepreneurial activity. A structured questionnaire was developed to capture the above linkages. To measure the latent variables, factor and reliability analyses were utilised. To examine the relationships, a regression analysis was performed on a unique dataset of respondents from three counties: Czechia, Hungary, and Serbia. The results show that personality traits positively influence motivation towards entrepreneurship. Furthermore, external barriers (ecological and technological issues), and infrastructure factors positively affect entrepreneurial motivation. From an academic viewpoint, personality traits and motivation to engage in entrepreneurial activity can be nourished by education, highlighting the role of universities in this regard. Our paper's findings should trigger the interest of policymakers who aim to introduce new instruments or change the existing ones (designing policies) to boost entrepreneurship.
Keywords: 350; business barriers; Czechia; entrepreneurial motivation; entrepreneurship; Hungary; infrastructure; personality traits; Serbia